Development of Instagram-Based Learning Media for Engineering Mechanics Subjects in The Construction and Property Field of SMK Negeri 3 Jombang - Iyaka Awala Firdaus; Isnandar Isnandar; Muhammad Aris Ichwanto (Jurnal Pendidikan Teknik Sipil, 2023)
Background: The use of technology needs to be increased in the Engineering Mechanics learning process, this is because the learning process carried out by teachers tends to be monotonous, apart from that the relevant school also does not provide textbooks as a learning tool which results in students not having reading books and only relying on notes sourced from learning. in the classroom. The lack of availability of teaching materials makes students passive in the learning process so that it can be said that the learning carried out is less effective. Therefore, this research aims to develop and analyze the feasibility of Instagram-based learning media as a breakthrough to overcome these problemsMethods: This research uses the Research and Development (R&D) method which applies the development model by Sugiyono. The data collection process entailed the usage of questionnaires to acquire primary data; on the other hand, the secondary data was utilised as supporting documentation.Results: The results in the form of an Instagram-based learning media product which obtained an assessment score from material expert validators of 93.94%, and media experts of 97.7% so that both are included in the very feasible category. . Meanwhile, the trials carried out on students obtained a score of 74.33% in the initial trial, and a score of 72.3% for the usage trial in the feasible categoryConclusion: Based on the results of the research that has been carried out, it can be concluded that Instagram-based learning media products for Engineering Mechanics subjects in the Construction and Property Business area of SMK Negeri 3 Jombang are suitable for use.